Epidemiological characteristics and genetic diversity of Bartonella species in rodents from southeastern China. (17th January 2022) - Liu, Haixin; Han, Tengwei; Liu, Weijun; Xu, Guoying; Zheng, Kuicheng; Xiao, Fangzhen
Abstract: Rodents are the primary hosts of Bartonella species and carry more than 22 Bartonella species. However, the information on epidemiological characteristics and genetic diversity of Bartonella species in rodents in southeastern China is limited. From 2015 to 2020, 1, 137 rodents were captured. Bartonella ‐positive DNA was detected in 14.9% (169/1, 137) of rodents by PCR for both the ssrA and gltA genes. A highest Bartonella prevalence was detected in Apodemus agrarius (33.5%) and lowest in B. indica (1.8%). The probability of Bartonella infection in summer (20.1%) was higher than in spring (14.6%; p  = .011, OR = 1.756). Sequencing and phylogenetic analysis revealed that nine known Bartonella species were identified in rodents, including B. tribocorum, B. grahamii, B. rattimassiliensis, B. queenslandensis, B. elizabethae, B. phoceensis, B. coopersplainsensis, B. japonica and B. rochalimae . In our study, Bartonella species exhibited a strong association with their hosts. Zoonotic B. tribocorum, B .  grahamii, B. elizabethae and B. rochalimae were found in synanthropic rodent species in southeastern China, which pose a potential threat to the public health. To prevent the spread of zoonotic Bartonella species to humans, preventive and control measures should be implemented, and more research is needed to confirm the pathogen's association with human disease.